2019
DOI: 10.1128/aac.01974-19
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of the Prevalence of Community-Onset Bloodstream Infections among Hospitalized Patients in Africa and Asia

Abstract: Community-onset bloodstream infections (CO-BSI) are major causes of severe febrile illness and death worldwide. In light of new data and the growing problem of antimicrobial resistance (AMR) among pathogens causing BSI, we undertook a systematic review of hospital-based studies of CO-BSI among patients hospitalized with fever. Without restriction to language or country, we searched PubMed, Web of Science, and Scopus for prospective hospital-based studies of culture-confirmed CO-BSI among febrile inpatients. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 80 publications
4
46
2
Order By: Relevance
“…The finding of S. enterica Typhi and Paratyphi A as the leading cause of BSI in Yangon is consistent with similar studies from other parts of South and South-East Asia [5,[36][37][38]. In a study of patients suspected to have enteric fever in Mandalay in central Myanmar during 2012-2013, S. enterica Typhi was isolated from 4.5% of blood cultures [35].…”
Section: Discussionsupporting
confidence: 82%
“…The finding of S. enterica Typhi and Paratyphi A as the leading cause of BSI in Yangon is consistent with similar studies from other parts of South and South-East Asia [5,[36][37][38]. In a study of patients suspected to have enteric fever in Mandalay in central Myanmar during 2012-2013, S. enterica Typhi was isolated from 4.5% of blood cultures [35].…”
Section: Discussionsupporting
confidence: 82%
“…Several more commonly reported bloodstream infections, including non-typhoidal serovars of Salmonella enterica, Staphylococcus aureus, Streptococcus pneumoniae, and Escherichia coli were also identified in this study population, but at lower relative frequency as compared to Brucella spp. 25,26 . Malaria was less prevalent than brucellosis in our study participants, as has been reported previously for northern Tanzania 46 .…”
Section: Discussionmentioning
confidence: 99%
“…2 In Southeast Asia in 2017, enteric fever incidence was estimated to be 219.8 per 100,000 populations and associated with 877,200 disability-adjusted life-year lost. 3 As with other countries in Southeast Asia, 4 Salmonella Typhi has been identified as a leading cause of community-onset bloodstream infection in the Lao People's Democratic Republic (Lao PDR), not only in the capital of Vientiane 5 but also in Luang Namtha in the northwest and Salavan in the south. 6 Furthermore, multiple-drug resistance has been identified among Salmonella Typhi isolates in Lao PDR.…”
Section: Introductionmentioning
confidence: 99%